2023
DOI: 10.1038/s41598-023-29107-9
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning with optical profilometry for GaN wafer screening

Abstract: To improve the manufacturing process of GaN wafers, inexpensive wafer screening techniques are required to both provide feedback to the manufacturing process and prevent fabrication on low quality or defective wafers, thus reducing costs resulting from wasted processing effort. Many of the wafer scale characterization techniques—including optical profilometry—produce difficult to interpret results, while models using classical programming techniques require laborious translation of the human-generated data int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Various non-destructive methods have been developed to characterize substrate imperfections, such as Raman spectroscopy, 11,12 Nomarski imaging, 7 and optical profilometry. 13,14 Photoluminescence (PL) mapping as a contactless, non-destructive, high-sensitivity inspection method has been implemented in recent years for the classification of a wide range of substrate-and epitaxy-related defects in GaN devices. 15,16 Compared to other characterization methods, PL mapping can detect signals related to radiative microstructures of the sample and perform quantitative analysis of specific defect types over a long range.…”
Section: Breakdown Characteristics Analysis Of Kv-class Vertical Gan ...mentioning
confidence: 99%
“…Various non-destructive methods have been developed to characterize substrate imperfections, such as Raman spectroscopy, 11,12 Nomarski imaging, 7 and optical profilometry. 13,14 Photoluminescence (PL) mapping as a contactless, non-destructive, high-sensitivity inspection method has been implemented in recent years for the classification of a wide range of substrate-and epitaxy-related defects in GaN devices. 15,16 Compared to other characterization methods, PL mapping can detect signals related to radiative microstructures of the sample and perform quantitative analysis of specific defect types over a long range.…”
Section: Breakdown Characteristics Analysis Of Kv-class Vertical Gan ...mentioning
confidence: 99%
“…ML has also been used to predict the quality of GaN Ohmic contacts from the fabrication recipe 9 . Previous work has shown that we can predict low voltage properties of vertical GaN diodes with over 75% accuracy from optical profilometry data using both convolutional neural networks 10 and simpler models 11 (logistic regression 12 , decision tree 13 , and K nearest neighbor 14 (KNN)). This work expands on this by using high voltage breakdown as the quality metric and discusses the possible defects causing reduced diode performance.…”
mentioning
confidence: 99%
“…Many types of defects affect the crystal structure in GaN, with a significant proportion discernable via observable morphological defects on the surface and small defects in the substrate that often extend through the epitaxial layers during growth. Hence, optical profilometry provides a data-rich input for developing ML models for wafer screening 11,[19][20][21][22] . This study involved the collection of optical profilometry data from seven GaN PiN diode wafers by employing a combination of data pre-processing and supervised machine learning algorithms to develop predictive models for different targeted performance metrics.…”
mentioning
confidence: 99%
See 2 more Smart Citations